Pengaruh Tehnik Akupresur Terhadap Penurunan Nyeri Punggung Bawah Pada lbu HamilUk 24 - 36 Minggu Di Desa Gayaman Mojokerto - Wahyuningrum, Tria; Yuswo Yani & Imam Zainuri, Lasiyati (JURNAL KEPERAWATAN BINA SEHAT, 2017)
AbstractDuring pregnancy lower hack pain caused by stretching and fatigue on the body due to uterine enlargement. According to some information to reduce the complaints are a wide variety of non-pharmacological measures that have been developed as guidance anticipation, TENS, distraction, relaxation, massage and acupressure in this case be an option to reduce lowerback pain. The purpose of this study to determine the effect of acupressure techniques on lower back pain in pregnant women 24-36 weeks gestation in Gayaman Village. The study design using analytical methods of pre experimental with pretest posttest design form of acupressure therapy as much as 2 times in 1 week. The samples of the research taken by using the total sampling, they consisted of 16 respondents. Analysis using crosstabs (cross tabulation). The results showed before acupressure (pretest) mostly moderate pain (56.25%) and after acupressure (posttesl) small part of pain (6.25%). To determine the intensity of pain before and after acupressure, by using a Bourbanis Scale. The results of theresearch indicates that Three is no effect of acupressure techniques on lower back pain in pregnant women 24-36 weeks gestation in Gayaman Village, Mojoanyar District, Mojokerto regency. So, to reduce lower back pain in pregnant women can be given acupressure with the administration to continue the appropriate time. This is to get the maximum results to the reduction of lower back pain in pregnant women.Keyword : Acupressure techniques. Lower Back Pain, Pregnancy